"Beras Merdeka": Branding lokal yang memperkuat identitas produk beras merah Desa Salobukkang - Henny Setyawati; M. Ilham Akbar Sabri; Rusdi; Marshanda Yuwinancy; Adnan; Minahari; Chaeril Syafri; Dwi Pramesti. Y; Henra Malik; Su’da Al Muntazah (Jurnal Dedikasi Masyarakat, 2024)
This service aimed to enhance the value of local brown rice in Salobukkang Village through innovative packaging and marketing. Local farmers faced challenges in packaging and product differentiation. A unique product combining brown and white rice was developed, offering balanced taste and nutritional benefits. The "Beras Merdeka" brand was created to represent local quality. Vacuum-sealed packaging protected the product and extended its shelf life. A comprehensive marketing strategy, including village government support, was implemented. This resulted in increased product value and appeal. By combining traditional farming with modern packaging and marketing, this service contributed to sustainable agricultural businesses.